Marketing Mix Strategies to Determine Purchasing Decisions for Fashion Products - Fatimah; Martaleni, Martaleni (Journal of Management Research and Studies, 2023)
The rapid development of the fashion business in Indonesia has led to high competition in the fashion business. In making purchasing decisions, consumers will be faced with several factors, one of which is the marketing mix factor. This study aims to examine the effect of the marketing mix on purchasing decisions. The research approach used is quantitative research with explanatory research. The variables in this study are product, price, promotion, place, and purchasing decisions. The research location is at Metro Busana Mojopahit. The population in this study were all buyers at Metro Clothing. The sampling technique was carried out using non-probability sampling technique, and a research sample of 90 respondents was obtained. Data analysis was carried out using multiple linear regression tests with SPSS software version 20. The results showed that product, price, promotion, and place partially and simultaneously had a positive and significant effect on purchasing decisions. The promotion variable is the variable that has the greatest effect on purchasing decisions. The results of the study indicate management to further maximize marketing given the increasingly fierce competition in the fashion business today.